Coherent phase control in electron-argon scattering in a bichromatic laser field - Zhou, Bin; Li, Shu-Min (Chinese physics, 2010)
This paper theoretically investigates the coherent phase control in electron-argon scattering assisted by a bichromatic laser field. The laser field is composed of a fundamental component and its second harmonic. The incoming and out going states of electron are described by the Volkov wave functions, and the electron-target interaction is treated as a screening potential. Numerical results for differential cross section of multiphoton processes vs the phase difference between the two components of laser field are discussed for several scattering angles and impact energies.